2003
DOI: 10.1046/j.1365-2230.2003.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-one cases of Marjolin's ulcer

Abstract: Marjolin's ulcer is a rare and often aggressive cutaneous malignancy that arises in previously traumatized or chronically inflamed skin, particularly after burns. We reviewed 264 burns cases treated in our departments to assess the frequency and clinicopathological features of this malignant complication. We found 31 cases of Marjolin's ulcer and a further 14 cases of nonmalignant ulceration at previous burn sites. Eighteen Marjolin's ulcers were located on the extremities, six on the scalp, six on the trunk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 18 publications
4
83
0
3
Order By: Relevance
“…The most common inciting injury in various studies has been the thermal injury and it stands true in our study as well [2]. Although no age is immune to development of MU, it has been reported that the latency period between the initial insult and development of MU is inversely proportional to the age at initial insult [8]. The mean latency period in our study was 12.0 ± 4.3 years which although falls within the range reported in literature but this is also because the range reported in literature is too wide.…”
Section: Discussionsupporting
confidence: 71%
“…The most common inciting injury in various studies has been the thermal injury and it stands true in our study as well [2]. Although no age is immune to development of MU, it has been reported that the latency period between the initial insult and development of MU is inversely proportional to the age at initial insult [8]. The mean latency period in our study was 12.0 ± 4.3 years which although falls within the range reported in literature but this is also because the range reported in literature is too wide.…”
Section: Discussionsupporting
confidence: 71%
“…4 and M.v.H., unpublished results). Furthermore, inflammation and chronic wounds are associated with development of human SCC, as in the development of SCC in burn scars, chronic venous stasis ulcers, and discoid lupus erythematosus (28)(29)(30). Progression of actinic keratosis to SCC has recently also been shown to be associated with an inflammatory stage (31).…”
Section: Discussionmentioning
confidence: 99%
“…4 Although initially described as a malignant transformation from a burn wound, the term Marjolin's ulcer has been used interchangeably for malignant transformation in any chronic wound, including pressure ulcers, osteomyelitis, venous stasis ulcers, urethral fistulas and anal fistulas. 2 Marjolin's ulcer may develop in various anatomical locations, although the highest incidence is in the lower extremities. 1,5 The predilection of these lesions may be due to injuries that affect the arms and legs, such as a grenade shrapnel injury in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Most Marjolin's ulcers are squamous cell carcinoma (SCC) in origin (over 75%) and have been associated with various types of chronic wounds, including pressure sores, osteomyelitis and venous stasis ulcers. 1,2 Few case reports in the literature exist regarding the malignant transformation of old war scars. We present a case of SCC arising from a grenade shrapnel injury sustained over 60 years prior in a Korean War veteran.…”
Section: Introductionmentioning
confidence: 99%